Pembelajaran IPA Inovatif Berbasis STEM - Islami, Anggun Variasi; Sunni, M. Abdurrahman (TSAQOFAH, 2024)
This research aims to see whether ICT-assisted STEM-based science learning can improve students' critical thinking and creative thinking skills. The population consisted of 3 classes and one class with a total of 28 students was selected. In students' critical thinking skills there was an increase from 68.15 to 82.44 and N-gain was 0.45 in the medium category. Students' creative thinking abilities also increased from 75.80 to 87.90 and N-Gain was 0.54 in the medium category. Referring to the results, it can be concluded that ICT-assisted STEM-based science learning can improve students' critical thinking and creative thinking skills so that students are expected to be able to compete in the very complex 21st century.